Lecture Notes on International Trade and Imperfect Competition - Anthony Venables (The Research Institute of Industrial Economics (IUI), 1996)
These notes discuss some of the main results and models from the theory of international trade under imperfect competition. They are necessairy both selective and superficial. Multinationals are conspicuous by their absence, and the reader is referred to Markusen (1995) for a recent survey. Up to date and exhaustive treatments of othe topics are provided in volume III of the the Handbook of international Economics, published in 1995.
Keywords: D51; F10; F12; 330; INTERNATIONAL TRADE; COMPETITION; Strategische Handelspolitik; Außenwirtschaftstheorie; Unvollkommener Wettbewerb; Theorie